2019
DOI: 10.1371/journal.pone.0222727
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis uncovers the limitations of current molecular detection methods for Fusarium oxysporum f. sp. cubense race 4 strains

Abstract: Fusarium oxysporum f. sp. cubense Tropical Race 4 (Foc TR4) is threatening banana production worldwide. Despite quarantine efforts, the pathogen continues to spread; thus, early diagnosis plays an essential role for the proper execution of contingency plans. Here, we assess the accuracy of four PCR-based molecular methods described in the literature for the identification and detection of race 4 strains, including Subtropical (Foc STR4) and Tropical Race 4 causing Fusarium wilt of banana. We screened a total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 57 publications
(106 reference statements)
0
51
0
Order By: Relevance
“…Primers developed for VCG 01213/16 were specific to Foc TR4 and did not detect false positives previously reported for other TR4 primers by Magdama et al . (2019) [ 49 ] (results not presented). It also did not amplify other Foc strains causing disease to Cavendish bananas in the tropics, such as the closely related Foc VCG 0121 [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primers developed for VCG 01213/16 were specific to Foc TR4 and did not detect false positives previously reported for other TR4 primers by Magdama et al . (2019) [ 49 ] (results not presented). It also did not amplify other Foc strains causing disease to Cavendish bananas in the tropics, such as the closely related Foc VCG 0121 [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…EC5-LR-GM1 shared identical TEF sequences with pathogenic isolates from Ecuador in lineage I + IV; but it is closely related to TR4 based on IGS sequences. Previous research showed that EC5-LR-GM1 is not pathogenic to Cavendish ‘Gran Naine’ and ‘Gros Michel’, but along with other endophytes, it shares genomic regions similar to those found in TR4 strains that have been exploited for PCR diagnostics leading to false positives [ 50 ]. Another interesting isolate was EC10-B-GM3, sampled from asymptomatic ‘Gros Michel’, with unresolved phylogenetic placement.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular techniques are the most frequently identification methods because of species specificity of this region. The technique is known to provide good resolution at the sub-species level, and thus sequence analysis is a superior choice for phylogeny in Fusarium species complexes [13,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…clinical isolates. In addition, ITS sequencing is known to provide good resolution and a superior choice for phylogenetic studies in the species complex [13,[37][38][39]. However, the high-throughput sequencing of Fusarium spp.…”
Section: Discussionmentioning
confidence: 99%